Predicting the role of organisational listening and job resources in job engagement - Jen, Sern Tham; Mohd Ali, Amirul Aizat; Thomas, Hongjie Zhang (Penerbit Universiti Kebangsaan Malaysia (UKM Press), 2022)
Job engagement is defined as one’s enthusiasm and involvement in his or her job. Individuals who are profoundly engaged with their job are motivated by the work itself. They will, in general, work harder and more productively than others and are bound to create the outcomes that their clients and organisation need. Although existing empirical studies have provided evidence that perceived organisational support (POS) and supportive leader behaviour can significantly predict job engagement, the effect of organisational listening on employee job engagement is still under researched. Guided by the Job Demand-Resources (JD-R) model, this study proposed that organisational listening is a vital predictor of job engagement. We analysed whether organisational listening holds a more substantial statistical power than perceived organisational support and supportive leader behaviour as job resources. We conducted an online survey that involved 207 employees from a Malaysian IT management consulting company. After analysing the survey data through multiple regression analysis, the results showed that organisational listening was a significant predictor of job engagement. Besides, organisational listening showed an incremental validity above and beyond perceived organisational support and supportive leader behaviour in predicting job engagement. These findings suggest that employees become engaged in their job when they believe that the leader incorporates values and action to listen accurately and is supportive. Implications in theoretical and practical perspectives were discussed. Keywords: Organisational listening, job engagement, job resources, perceived organisational support, supportive leader behaviour.